Solid state fermentation for the production of lipolytic fungal enzymes - Romano, D.; Gandolfi, R.; Gualandris, R.; Romano, A.; Starace, F.; Villa, Raffaella; Molinari, F. (Univ. of Milan Department of Food Science and Microbiology, 2007)
The production of lypolitic moulds in solid state fermentation was studied. Aspergillus oryzae and Rhizopus oryzae were grown on rice hulls using different media. Tween 80 and olive oil were employed as main carbon sources; the whole solid cultures were lyophilised and employed in heptane for catalysing the formation of various geranyl esters with molar conversions ranging from 40 to 95%, under optimised conditions, starting from 50 mM geraniol and equimolar amount of the acid.
Keywords: solid state fermentation rice hulls Rhizopus oryzae Aspergillus oryzae esterification flavours polyurethane foam colletotrichum-truncatum aspergillus-oryzae inert carrier culture lipase mycoherbicide efficient mycelium support